Ecological factors influencing the beneficial endosymbionts of the hemlock woolly adelgid (Hemiptera: Adelgidae). (27th September 2017) - Mech, Angela M.; Harper, Sherilyn J.; Havill, Nathan P.; von Dohlen, Carol D.; Burke, Gaelen R.
Abstract: Bacterial endosymbionts of sap‐sucking insects provide their host with a number of beneficial qualities, including the supply of nutrition, defense against parasitoids, and protection from heat stress. Damage to these bacterial associates can therefore have a negative impact on the fitness of their insect host. We evaluated observational and experimental factors regarding the nonnative hemlock woolly adelgid ( Adelges tsugae Annand) (Hemiptera: Adelgidae) to help understand the roles of its three recently identified symbionts, including under heat stress conditions. The prevalence of A. tsugae 's facultative symbiont ( Serratia symbiotica ) was examined at different spatial scales to determine how variable infection rates are for this symbiont. There was no significant difference found in infection rates between adelgids on a tree, within a plot, or within a state. However, significantly more adelgids in Georgia (95%) had S. symbiotica compared to those in New York (68%). Microsatellite genotyping of the adelgids found that this difference was most likely not the result of a second introduction of A. tsugae into eastern North America. Comparison of S. symbiotica proportions between first and fourth instars showed that symbiont absence did not affect the ability of A. tsugae to survive aestivation. Evaluations of symbiont densities within each adelgid found that when S. symbiotica was absent, the density of obligate symbionts was significantly higher. Exposure to heat stress (32.5 °C) was not consistently correlated with changes in symbiont densities over a 4‐d period. Overall, we have shown that symbiont prevalence and densities vary within the broad population of A. tsugae in eastern North America, with potentially significant effects upon the ecology of this important pest.